Market forces - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Isah Alhassan of the University of Abuja, Nigeria, emphasises the importance of marketing for the farmer: 'A knowledge of marketing and its problems will help the farmer make decisions which are important to him either in the operation of his own...